Development Of Children's Worksheets In Improving Cognitive Development Of Children Age 5 – 6 Years - Kartika Ananda; Arofi, Wulan (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of the implementation of this research is to obtain a children's worksheet (LKA) that is in accordance with the rules set by the Ministry of National Education (now the Ministry of Education and Culture) to facilitate children in learning, children can understand the material and achieve children's cognitive development during learning at school through LKA. The development model of this research uses descriptive procedural capital developed by Borg and Gall. Questionnaire in R&D is used to get answers on the feasibility and validity of the product from the validators to be used as an improvement for researchers. Through this questionnaire, the researcher will improve the product, then after it is completed, this R&D product is ready to be implemented at the Pembina Jekan Raya State Kindergarten. In this study, a learning outcome acquisition test will be used by comparing the results of the pre-test and post-test to show the effectiveness in learning after using LKA. The pre-test was carried out when the initial trial with 8 children and the post-test was carried out during the field trial with 8 children. Based on the results of the teacher response validation questionnaire, the feasibility level of LKS/LKA development products in the initial trial has been in theVERY VALID category. These results conclude that the development of worksheets for 5-6 year old children at Pembina Jekan Raya State Kindergarten can improve cognitive development.